TAFSIR AHL-DZAUQ WA AL-IRFAN LATAIF AL-ISYARAH AL-IMAM AL-QUSYAYRI AL-NAISABURI (376 H/986 M - 465H/1075M) - Ali Aljufri (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2020)
Al-Qur'an interpretation of Sufi nuances is developing rapidly, especially after the prominent figure of the theoretical Sufi interpretation (nazhari) Muhiddin Ibn Arabi (w.638 H), one of which is a practical Sufi interpretation (amali or faudhi) by Abu al-Qasim Abd Karim bin Hauzan bin Abd Malik al-Qusyayri al-Nesyapuri. One of the figures in the renewal of classical Sufi interpretation that offers a new method of interpretation is the bayani isyari mujaz method which emphasizes the aspects of the Qur'anic cues from the implied meaning (inner) with the approach of language (literature) to the text as a discussion of the miracle of literary language in the Koran. Al-Qusyayri's attention is not merely a gesture or vocabulary of the Qur'an. he has an open view of how to combine the science of Shari'a and the nature of interpreting the Holy Qur'an.